Unveiling the link between inequality and poverty - Casas Herrera, Julian Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper attempts to reveal the relationship between inequality-poverty from the exposure of empirical and theoretical elements, which allows, on the one hand, to outline that the approach of both phenomena has generally been isolated; and on the other, to expose a proposal that shows the importance of recognizing the relationship between inequality-poverty to improve the society well-being. To validate the proposal, a simulation was carried out in which the instrumentalization of the Gini coefficient and the Poverty Lines was involved, showing as a result the existence of the relationship and that when applying redistribution mechanisms, such as limiting the tolerance threshold of inequality of income, poverty is reduced. Therefore, it is essential to defend the right to live in a more egalitarian society, since poverty persists, fundamentally, because of inequality.